Diseño de perfiles de competencias para los puestos claves del proceso de cirugía cardíaca en el Cardiocentro ''Ernesto Che Guevara'' - Martínez Roque, Daimarelis (Universidad Central "Marta Abreu" de Las Villas, 2015)
This research is conducted at the Heart "Ernesto Che Guevara" of Villa Clara. It pursues the same purpose design competency profiles for key positions in the process of heart surgery, from the application of a procedure for identifying them. On the eve of achieving this objective, a diagnosis of the current situation of Human Capital process was conducted, specifically related to the analysis and description of the job and the main processes of human capital management competencies as: selection and integration, training and development and performance evaluation. Among the main techniques and / or methods used in the research are document analysis, direct observation, interview, checklist, the Delphi method rounds and proposed in the literature of Sotolongo Sanchez (1998) procedure. With the above profile obtained as a result of competition for key positions in the process of cardiac surgery, specifically the specialist in 1st or 2nd degree of Cardiovascular Surgery and the Deputy Director of Cardiovascular Surgery at the target institution study.
Keywords: Análisis y Descripción de Puestos de Trabajo; Gestión del Capital Humano; Selección e Integración; Capacitación y Desarrollo; Evaluación del Desempeño Integral; Servicio de Cirugía Cardiovascular; Calidad de los Servicios Prestados; Competencias Laborales; Cardiocentro “Ernesto Che Guevara”; Villa Clara